Effects of a novel differential diagnosis aid for managing patients with unexplained fatigue in primary care: a prospective randomized, controlled, open and multicenter study in primary care - Roland von Känel; Stefan Neuner-Jehle; Reto W. Kressig; Idris Guessous; Pierre Alexandre Krayenbühl; Lukas Zimmerli; Anne Angelilo-Scherer; Thomas Keller; Caroline Elzner; Karl Pauls; Neige Morin; Edouard Battegay (BMC Primary Care)
Abstract Aims of the study Unexplained fatigue is a common reason for encounters in primary care. However, currently no aid orients physicians in detecting its potential causes. The aim of this study was to evaluate whether the novel Fatigue Differential Diagnostic Aid (FDDA) supported clinicians in better managing unexplained fatigue. Methods This was a prospective, cluster-randomized, controlled, open, and multicenter study comparing the use of the FDDA vs usual care in patients with unexplained fatigue as the main reason for encounter. The primary endpoint was difference in Patient Global Impression of Change (PGIC) between groups at 3 months. Among pre-defined secondary endpoints were: Difference in change of PGIC between groups at 6 months; percentage of patients with fatigue reduction; mean reduction in fatigue; clinician’s confidence in diagnosis; patient satisfaction with quality of care (diagnostic process and treatment); number of clinician-reported visits; number of referrals to specialists; and time until final diagnosis. Results 112 primary care practitioners (PCPs) recruited in Switzerland between 2017 to 2020 were randomly cluster-assigned to the FDDA = 57 or usual care = 55 arm. Of these, 15 (FDDA) and 22 (usual care) PCPs recruited 93 patients (FDDA: n = 40, usual care: n = 53). The achieved sample size was less than planned. There was no difference in PGIC at 3 months between groups (D = 0.06, 95%-CI: -0.41 – -0.53, p = 0.802). Among secondary endpoints, no significant differences occurred in PGIC at 6 months, nor in fatigue reduction. However, in the FDDA group, more patients reported less fatigue at 3 or 6 months (D = 18.9%, 95%-CI: -33.6 – -4.3%, p = 0.011), and increased satisfaction with treatment management at 1 month (FDDA 56.8% vs usual care 25.0%, p = 0.004) and 3 months (FDDA 64.9% vs usual care 31.0%, p = 0.003); the FDDA was also associated with higher total number of visits (median 4.0 vs 3.0, p < 0.001). Conclusions In this pilot study, the FDDA, a structured diagnostic aid for guiding PCPs in identifying the causes of unexplained fatigue in their patients, was not able to show a global improvement in patient outcomes despite improvements in fatigue and satisfaction with care. The evaluation of fatigue in larger-scale studies is warranted. Trial registration This trial was retrospectively registered on ClinicalTrials.gov. Trial registration number: NCT05861492. Date of registration: 17th May 2023. The ethics committee of Ethikkommission Nordwest- und Zentralschweiz (EKNZ) had originally voiced the opinion that no registration was required because no drug or intervention was involved, i.e., the study was non-interventional and observational. However, the study authors felt that the study should be retrospectively registered because the FDDA could be interpreted to be an active intervention. At the time of registration, two protocol deviations occurred that are explicitly addressed in the Methods section of this manuscript. Because of the low sample size, we statistically compared “patients” instead of “comparing patients nested in doctors” (the latter was performed as an additional analysis). Thus, cluster randomization was performed, but the analysis to consider this was not feasible.